New Approaches to Data-Driven Civilian Oversight of Law Enforcement: An Introduction to the Second NACOLE/CJPR Special Issue. (March 2018) - Stageman, Daniel L.; Napolitano, Nicole M.; Buchner, Brian
In April of 2016, National Association for Civilian Oversight of Law Enforcement (NACOLE) and John Jay College partnered to sponsor the Academic Symposium "Building Public Trust: Generating Evidence to Enhance Police Accountability and Legitimacy." This essay introduces the Criminal Justice Policy Review Special Issue featuring peer-reviewed, empirical research papers first presented at the Symposium. We provide context for the Symposium in relation to contemporary national discourse on police accountability and legitimacy. In addition, we review each of the papers presented at the Symposium, and provide in-depth reviews of each of the manuscripts included in the Special Issue.